Consumer contracts in the European Court of Justice case law. Latest trends - Calvo Caravaca, Alfonso-Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The concept of “consumer” is, in theory, a restrictive concept. However, the ECJ has now extended it to cases in which a private individual has gone on to practice as a professional in an manifest, public and conspicuous manner. Judgment ECJ 25 January 2018, C-498/16, Facebook proves it. In relation to consumers of financial products, the ECJ skillfully pulls strings in the context of art. 7.2 BR I-bis; however, that norm is totally insensitive with regards to the consumer. The future is stepping forward towards online mass consumption, and in the present virtual social landscape it is necessary for the ECJ to open up new ways of protecting the consumer that keep up with times. In this context, it is necessary that future amendments to the Brussels I-bis Regulation incorporate the concepts that the ECJ has created in relation to jurisdiction in the cross-border consumer sector: the concepts of “act of consumption”, “consumer”, “professional”, and “directed activity”, for example, should stop being jurisprudential concepts to become legal concepts.
Keywords: act of consumption; consumer; consumer contract; cross-border consumer sector; directed activity; dual contracts with both private and professional purpose; (international) jurisdiction; Private International Law; professional